Physicochemical, functional, and bioactive compounds characterization of mucilage from irrigated Opuntia spp. and its application as an edible coating - Luna Zapién, Edén Arelí (Universidad Autónoma Chapingo, 2023)
Plants of the genus Opuntia spp. occupy a preponderant place due to their ability to adapt to extreme climatic conditions. Cladodes are an important source of mucilage, which is a promising compound to be used as an agro-industrial additive. Three irrigation regimes were tested: non-irrigated (rainwater), supplemental irrigation where plants were irrigated at field capacity (0.28 m3 m-3 ) when soil water content reached the permanent wilting point (0.14 m3 m-3 ), and full irrigation (100 % of the evapotranspiration of the crop) on 'Amarilla Olorosa', 'Cristalina', 'Dalia Roja' and 'Roja Lisa' varieties of prickly pear cactus. The cladodes of these varieties were collected to extract and purify the mucilage. The mucilage was characterized in terms of yield, color, chemical composition, infrared spectroscopy, viscosity, molar mass, functional properties, total polyphenols, and antioxidant capacity. The structure of the mucilage obtained corresponded to a xyloglucan skeleton with arabinose ramifications. In general, the mucilage of 'Amarilla Olorosa' and 'Roja Lisa' plants under no irrigation produced the highest mucilage content, better lightness, carbohydrate, fiber content, relative water content, and solubility; while parallelly, the ash content was lower compared to the mucilage from 'Cristalina' and 'Dalia Roja' varieties. The mucilage of the 'Amarilla Olorosa' plants under no irrigation was the most viscous. On the other hand, the mucilage powder of the non-irrigated 'Cristalina' variety had the highest swelling index with high concentrations of total polyphenols and antioxidant capacity. Therefore, this mucilage, along with sodium alginate, was used to elaborate an edible coating. This coating was useful to preserve the commercial quality of avocado halves. Therefore, water restriction in prickly pear cactus plants of the varieties studied here, is a feasible strategy to produce mucilage with physicochemical characteristics relevant for agro-industrial purposes.
Tesis (Doctorado en Ciencias en Recursos Naturales y Medio Ambiente en zonas Áridas)
Keywords: Opuntia spp.; cladode; heteropolysaccharide; sugars; antioxidants; coating films.